القرآنية في شعر رضا الخفاجـي مجموعة (( كربائيلو )) نموذجاً - م.د فاضل حمد مكوار (Thi Qar Arts Journal, 2021)
This study aims at finding out the effects of the miraculous text of the Holy Quran with its construction, contents, indications, significance , allusions, and its explicitly in the new textual construction through employing vocabularies , and the Qur’anic structure directly, whether it is in its conformity or not without any modifications; or indirectly accompanied by indicative and illusionistic modification by absorbing the text in a new structural environment, then discovering the reference it descends from . This is due to the great role that the Qur’anic system plays in the context of the creative image in prose and poetry. The study limits itself to the poetic output of the poet Reda Al-Khafaji through one model, of his poetic collection “Karbalaio Beit Al-Rab” which depicts the painful incident of Al-Taff, and the holy city of Karbala, with all its events and characters through a significant reference to the Qur’anic text from which the poetry of this poet is called for , prepared and consulted